SISTEM PEMBIAYAAN SOSIAL BERBASIS KOMUNITAS - ERA SONITA; AHMAD WIRA (Al-Masraf: Jurnal Lembaga Keuangan dan Perbankan, 2019)
Islamic cooperative is a financial system based on social and solidarity, where its characteristics are different from other financial institutions. This social financial institution is a set of interdependent relationships between financial and social. This paper explains about how the institutional economy in this case the Islamic cooperative understands the form of interaction between individuals, organizations in establishing mutually supportive relationships. What is the form of sustainability of Islamic cooperative financial institutions through its ability to respond to the needs of its members towards the needs of venture capital without applying interest and profit sharing. In the sense of the word form of work of this Islamic cooperative institution based on the concept of help to help members of the cooperative.